Neonatal vaccination of low birthweight infants in Ghana. Issue 2 (13th October 2016) - O'Leary, Maureen; Edmond, Karen; Floyd, Sian; Hurt, Lisa; Shannon, Caitlin; Thomas, Gyan; Newton, Sam; Kirkwood, Betty; Thomas, Sara
Abstract : Objectives: Global vaccination policy advocates for identifying and targeting groups who are underserved by vaccination to increase equity and uptake. We investigated whether birth weight and other factors are determinants of neonatal BCG vaccination in order to identify infants underserved by vaccination. Methods: We used logistic regression to calculate adjusted ORs (AORs) for the association between birth weight (categorised as non-low birth weight (NLBW) (≥2.50 kg) and low birth weight (LBW) (2–2.49 kg, 1.50–1.99 kg and <1.50 kg)) and non-vaccination with BCG at the end of the neonatal period (0–27 days). We assessed whether this association varied by place of delivery and infant illness. We calculated how BCG timing and uptake would improve by ensuring the vaccination of all facility-born infants prior to discharge. Results: There was a strong dose–response relationship between LBW and not receiving BCG in the neonatal period (p-trend<0.0001). Infants weighing 1.50–1.99 kg had odds of non-vaccination 1.6 times (AOR 1.64; 95% CI 1.30 to 2.08), and those weighing <1.50 kg 2.4 times (AOR 2.42; 95% CI 1.50 to 3.88) those of NLBW infants. Other determinants included place of delivery, distance to the health facility and socioeconomic status. Neither place of delivery nor infant illness modified the association between birth weight and vaccination (p-interaction all >0.19). Facility-born infants were vaccinated at a mean of 6 days, suggesting that they were not vaccinated in the facility at birth but were referred for vaccination. Conclusions: LBW is a risk factor for neonatal under-vaccination, even for facility-born infants. Ensuring vaccination at facility births would substantively improve timing and equitable BCG vaccination.